Determinants of employee psychological ownership and its impact on sustainable manufacturing performance - Hanif Mauludin; Hegi Harjoyo; Darti Djuharni (Universitas Hayam Wuruk Perbanas, 2023)
This study aims to examine the determinants of employee psychological ownership and its effect on sustainable manufacturing performance. The population in this study is employees of a cigarette company in Indonesia. The sample used is 100 respondents, consisting of workers, supervisors, front line managers, and senior managers of a large cigarette company in Indonesia who are involved in initiative programs to achieve sustainable manufacturing performance. The sampling technique used is purposive sampling. Data collection is carried out by distributing questionnaires directly to respondents and conducting focus group discussions (FGDs). The analytical tool used is Partial Least Squares with SmartPLS version 3. The results show that Servant Leadership has a significant effect on Growth Mindset and Capability Building; Growth Mindset and Capability Building have a significant effect on Employee Psychological Ownership; and Employee Psychological Ownership has a significant effect on Sustainable Manufacturing Performance. Therefore, to achieve sustainable manufacturing performance, it is necessary to have a strong employee psychological ownership by forming a mindset to always grow, accompanied by increasing individual capabilities through effective servant leadership.